Racial wealth disparities: Is the gap closing? - Edward N. Wolff (Levy Economics Institute of Bard College, 2001)
Despite decades of policies aimed at improving the economic position of African Americans in terms of relative income and earnings, they remain substantially behind whites. The research presented in this brief indicates that the wealth gap is even more staggering. Following families over time in order to understand racial differences in the sources and patterns of wealth accumulation, Senior Scholar Edward N. Wolff finds that African Americans would have gained significant ground relative to whites in the past 30 years if they had inherited similar amounts, comparable levels of family income, and more similar portfolio compositions. Therefore, even if the income gap between whites and African Americans were immediately eliminated, it may take another two generations for the wealth gap to close. However, certain policies could help speed up the process.
Keywords: 330; Vermögensverteilung; Schwarze; Ethnische Gruppe; USA